2012
DOI: 10.1155/2012/672162
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Sleeve and Micronutrients Supplementation: Our Experience

Abstract: Background. Laparoscopic gastric sleeve (LGS) has been recently introduced as a stand-alone, restrictive bariatric surgery. Theoretically, LGS attenuates micronutrients deficiencies and associated complications that were typically observed following malabsorptive procedures. The aim of this study was to assess some micronutrients and mineral deficiencies in patients undergoing LGS. Methods. In the period between July 2008 and April 2010, 138 obese patients (110 females and 28 males) with mean BMI 44.4 kg/m2 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
3
30
1
1
Order By: Relevance
“…Thirteen studies showed a mean 25(OH)D level < 20 ng/ml at 6 months to 11 years post operatively [51,54,55,64,78,8592]. The remaining studies, almost half, reported a 25(OH)D level between 20 and 30 ng/ml [53,5659,62,6771,76,77,79,93–100]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen studies showed a mean 25(OH)D level < 20 ng/ml at 6 months to 11 years post operatively [51,54,55,64,78,8592]. The remaining studies, almost half, reported a 25(OH)D level between 20 and 30 ng/ml [53,5659,62,6771,76,77,79,93–100]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 25(OH)D level did not change [67,68,76] or even decreased [64,72,78] in several studies at one year follow up, despite supplementation (equivalent daily dose range 200–800 IU) (Figure 3, Appendix). Avgerinos et al showed an initial increase followed by a drastic decrease in 25(OH)D level at 1 year following RYGB, despite sustained vitamin D supplementation of 800 IU daily; findings that remain unexplained [80].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that LSG has a minimal impact on macronutrients as it does not alter the site of their absorption in the small intestine [ 39 ]. Gehrer et al compared the nutritional defi ciencies occurring after LSG and laparoscopic RYGB and observed nutritional defi ciencies in 57 % of patients.…”
Section: Nutrient Defi Ciencies After Lsgmentioning
confidence: 99%